Fermentation Influences the Total Flavonoid Content and Antioxidant Activity of Syzygium polyanthum - Saputri, Aurya; Christian, Yulius Evan; Hidayati, Nurul; Indah, Indah; Setiawansyah, Arif (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2024)
Introduction: Syzygium polyanthum are widely recognized for their rich phytochemical profile, including flavonoids and phenolics. However, the bioavailability of these compounds can be limited, prompting exploration of methods to enhance their accessibility and potency. Aims: This study investigates the effects of fermentation on the bioactive compounds and antioxidant properties of Syzygium polyanthum. Methods: Three sample groups were examined: fresh leaves, leaves fermented for 3 days, and leaves fermented for 5 days. Qualitative and quantitative analyses were conducted to assess flavonoid content, phenolic compounds, and antioxidant activity in each sample. Result: The results demonstrated that fermentation significantly impacted these properties, with the 5-day fermented sample exhibiting the highest values: total flavonoid content of 279.850 mg QE/g, total phenol content of 135 mg GAE/g, and antioxidant activity with an IC50 of 51.89 ppm. Conclusion: These findings suggest that fermentation can be an effective method to enhance the nutritional and medicinal properties of Syzygium polyanthum leaves. This research provides valuable insights into the potential applications of fermented Syzygium polyanthum in the food and pharmaceutical industries, paving the way for further exploration of its health-promoting properties.